2017
DOI: 10.5539/ijef.v10n1p13
|View full text |Cite
|
Sign up to set email alerts
|

The Liquidity of Bitcoin

Abstract: This paper studies the liquidity of Bitcoin using the time series daily data over the period 1/1/2014 to 12/31/2015. Based on the available data for Bitcoin, five liquidity measures are chosen to compare the liquidities among five Bitcoin exchanges and the liquidities of different sizes of stocks. The results suggest that the liquidity of Bitcoin depends on the choice of the Bitcoin exchanges, and Bitfinex, one of the Bitcoin exchanges, provides the highest liquidity for Bitcoin trading. Moreover, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Likewise, the price dynamics of Bitcoin show evidence of strong volatility and heavy tail behavior which seem to differ fundamentally from classic currencies, see for example Baur et al (2018); Osterrieder and Lorenz (2017); Carrick (2016); Kasper (2017) and Osterrieder (2017); Chan et al (2017). To some extent these peculiarities can be attributed to market liquidity which cannot compete with classic securities exchanges and which varies across Bitcoin exchanges, see (Loi, 2017). Nonetheless, Bitcoin is increasingly perceived as a viable alternative investment opportunity with potential for portfolio diversification and risk hedging, see for example Chuen et al (2017); Brière et al (2015); Dyhrberg (2016); Petukhina et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the price dynamics of Bitcoin show evidence of strong volatility and heavy tail behavior which seem to differ fundamentally from classic currencies, see for example Baur et al (2018); Osterrieder and Lorenz (2017); Carrick (2016); Kasper (2017) and Osterrieder (2017); Chan et al (2017). To some extent these peculiarities can be attributed to market liquidity which cannot compete with classic securities exchanges and which varies across Bitcoin exchanges, see (Loi, 2017). Nonetheless, Bitcoin is increasingly perceived as a viable alternative investment opportunity with potential for portfolio diversification and risk hedging, see for example Chuen et al (2017); Brière et al (2015); Dyhrberg (2016); Petukhina et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Kim ( 2017 ) and Dyhrberg et al ( 2018 ) suggested that BTC’s attractiveness for retail trading lies in its lower transaction costs. Loi ( 2018 ) also regarded various exchanges to compare liquidity. By implementing different low-frequency liquidity indicators, the author found that BTC’s liquidity is typically lower than stocks and that liquidity differs throughout exchanges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By closely relating to this strand of literature, we found many empirical studies documenting the linkage between trading volume and returns in the cryptocurrency market, indicating the need for exploring the determinants of trading activity (Bouri et al 2019c ). Many studies capitalized on transaction data for capturing liquidity in the cryptocurrency market while mainly focusing on BTC, such as Loi ( 2018 ), Wei ( 2018 ), and Brauneis and Mestel (2018). Overall, this literature strand has explored various facets of cryptocurrency liquidity and predominantly investigates the linkage between liquidity and efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from significant market inefficiency suggesting existence of profit opportunities, cryptocurrency markets are also known to be susceptible to bubbles, leading to frequent bear markets [5], [59]. Additionally, liquidity is frequently a concern there [60], [61]. Those factors were found to contribute positively to pairs trading performance in traditional stock markets, and cryptocurrencies are also unique in the wide-spread availability of highfrequency data, which is another area in which pairs trading appears to be successful.…”
Section: Literature Reviewmentioning
confidence: 99%